A Study of the production system of Am-Europharma Corporation - Buyco, Joyce Dawn S. (College of Engineering, 2002)
This production and/or Operations Management study is conducted on Am-Europharma Corporation, a local company producing a wide range of pharmaceutical products. The end goal of this study is to achieve goal congruence in every aspect of the company by analyzing the current system, identifying the problems and weaknesses, and proposing ways for improvement. The three major problems experienced by the company are unreliable forecasting, large stock outs of raw materials and high production cost per unit. However, the identified root problems of all the other problems are unreliable forecasting and absence of safety stock level for raw materials, which when given appropriate solution(s) will automatically solve, in one way or another, all the other problems identified. After analyzing and evaluating the proposed alternatives, the group recommends the use of simple moving average as forecasting technique for both capsules and liquids, which has n=5 and n=7, respectively. a safety stock level for raw materials was also determined together with the target inventory level. And lastly, a proposed layout was presented that will minimize the material handling costs for each operation.